Simple methods to predict the minimum baking time of bread - Purlis, Emmanuel (2019)
Baking is a complex transformation process since many coupled physical phenomena take place within the product. For practical industrial purposes, it would be desirable to count on simple methods to predict accurately the process time. Unlike food preservation operations, two different process times can be defined: the critical or minimum time is determined by the complete dough/crumb transition and ensures the acceptability of the product; the quality time is given by a target value of a certain sensory attribute (e.g. surface colour), and it is associated with preference of consumers. Despite the existing physics-based models which aim to describe comprehensively the baking process, there is a gap between academic knowledge and the industrial practice and needs of design engineers. Therefore, in this work we explore three simple methods to predict the minimum baking time of bread, which are based on a previously developed and validated heat and mass transport model. All three simple methods (two heat transfer models and one regression equation) predict very well the critical time for a wide and common range of operating conditions; mean absolute relative error is 3.61%, 1.17% and 0.30%, respectively. The degree of difficulty regarding implementation of simple methods is also discussed. Finally, it is demonstrated that heat and mass transfer can be decoupled for certain calculations, by using appropriate simplifications based on knowledge of transport phenomena governing the process.